An Assessment of Heavy Metal Concentrations in Surface Sediments from the Knysna Estuary - Armitage, Michael Philip Anthony (Department of Environmental and Geographical Science, 2023)
This research presents an analysis of surficial sediment samples in respect of total heavy metal concentrations, sediment grain size, and total organic carbon within 36 surface sediment samples from the Ashmead Channel in the Knysna Estuary. 15 surface sediment samples were also analysed from Chongming Island in the Yangtze Estuary of the People's Republic of China, and the results compared between the two systems, in addition to other South African and global estuaries with similar characteristics to Knysna. Metals analysed were Cr, Cd, Cu, Zn, Hg, As, and Al. Statistical analyses, including Pearson's Product–Moment correlation, enrichment factor analysis, and the assessment of heavy metal contamination were conducted between the variables to determine patterns of difference and similarity between the sites, as well as to determine the degree of contamination in the Knysna sediments. Results from Knysna were also compared to those from previous studies in the area. This study found that the Knysna sediments are not highly contaminated with heavy metals in relation to South African Revised National Action List levels, however, the degree of enrichment in the sediment has increased by a substantial margin over the past 20 years. Mean metal concentrations in Knysna are Cr: 7.37mg/kg, Cd: 1mg/kg, Cu: 6.43mg/kg, Pb: 7.43mg/kg, Zn: 57.4mg/kg, Hg:< 1 mg/kg, As: < 1mg/kg, and Al: 2138mg/kg. Mean enrichment factor classes of the concerning metals are Cr: 1.69, Zn: 3.89, Pb: 2.56, and Cu: 2.33. Upon comparison with sediments from Chongming Island, it was noted that the sediment in the Yangtze has much higher background heavy metal concentrations than Knysna. The study also found that the degree of enrichment in relation to background concentrations for the sediment sites in Knysna was surprisingly similar to that seen in the Yangtze estuary for select metals, despite the Yangtze being a highly polluted system. It must be noted that the results from the Ashmead Channel likely indicate greater contamination than what is present in the entire Knysna Estuary, due to the close proximity of a number of contaminant sources, as well as flow restrictions. The Yangtze also experiences much higher sediment accumulation rates, therefore reducing the degree of enrichment. This study, therefore, shows the value of frequent contaminant monitoring in the Knysna Estuary and recommends that additional work be conducted in the system to develop the picture of heavy metal contamination, in addition to other pollutant enrichment, in the system. Furthermore, this study demonstrates that the comparison of different estuarine environments can be a useful tool for understanding the severity of heavy metal contamination in these systems.